The international tourists on Trans-Siberian Railway : tourist typologies, motivational factors and tourist experience - Larionov, Hanna (My University, 2019)
The idea for this study came when my friends told me that they would travel the Trans-Siberian Railway (TSR). I started to wonder what kind of travel experience TSR was and what kind of tourists end up doing the trip. So, this study sets out to examine, analyse and provide a holistic description of TSR and how it is experienced by international tourists. More precisely, the aim is to understand what type of tourist chooses to travel the TSR and what are the underlying motivations driving these particular individuals. In order to facilitate my research proses, analysis, and conclusions I reviewed different theories suggested for creating tourist typologies as well as theories conceptualizing motivation behind travelling and factors impacting tourist experience. Due to the lack of academical research on TSR from the tourism perspective, I decided to do a qualitative study using an ethnographic research approach. In an ethnographical study researcher usually submerges themselves into the field and uses observation and own experiences as a tool for learning about the phenomena they are studying. The data for this study was collected during a 28-day long research trip on TSR, using in-depth theme interviews, participant observation, pictures, videos and travel diary. I spent a considerable amount of time whit most of the interviewees in addition to the interview situation. The observations I made during this time helped to provide more comprehensive insight because sometimes what people say in the interview may differ from their actual actions. Thirteen international tourists from nine different countries were interviewed for this study. Based on the demographic and psychographic segmentation criteria I suggest 4 different typologies in which I could roughly divide the interviewed tourists: Young and Hungry, Opportunists, Globetrotters and Seasoned Travellers. I found out that what drew these tourists towards Siberia was the mystery and novelty and for some doing it had been a dream for a long time. Because the travellers did not have much knowledge or expectation about TSR they were generally positively surprised about it. What seemed to bring experiential value to the tourists were the unique interactions they had with the locals and other travellers and the feeling of accomplishment from travelling the world’s longest railway. As travelling becomes more popular people will be looking for new destinations that can provide them whit a certain amount of novelty and excitement. For this reason, I believe that Russia, especially the less “westernised” part such as Siberia, will attract more tourist. Russia should acknowledge the tourist market potential of TSR and encourage the tourist establishments, travel agencies and RZD (Russian National Railway Company) to develop their services in order to make the trip more attractive.

Saini idean tutkimukselleni, kun ystäväni kertoivat matkustavansa Venäjän halki junalla Trans-Siperian rautatietä (TSR) pitkin. Mietin millainenkohan matkailukokemus TSR oli ja millaiset turistit päätyvät matkustamaan sillä. Joten tämän tutkimuksen tarkoitus on tutkia, analysoida ja antaa kokonaisvaltainen kuvaus TSR:stä ja siitä, miten kansainväliset turistit kokevat sen. Tavoitteena on myös ymmärtää, minkä tyyppiset turisti valitsevat tämän matkakohteen ja mitkä ovat motiivit tämän valinnan taustalla. Helpottaakseni tutkimusprosessia sekä analyysin ja johtopäätösten tekemistä tarkastelin erilaisia turistitypologioiden luomiseen ehdotettuja teorioita sekä teorioita, jotka käsittelevät matkustusmotivaatiota ja matkailukokemukseen vaikuttavia tekijöitä. Koska TSR:stä ei juurikaan ole tehty aikaisempaa turismiin liittyvää akateemista tutkimusta, päätin tehdä laadullisen tutkimuksen ja käyttää etnografista tutkimuslähestymistapaa. Osallistumalla itse tutkittavaan ilmiöön, etnografi käyttää havainnointia ja omia kokemuksia työkaluna pyrkiessään tarkastelemaan, kuvailemaan ja ymmärtämään tutkimaansa kohdetta. Tämän tutkimuksen aineiston keruu tapahtui TSR:llä 28 päivän pituisella tutkimusmatkalla. Tiedon keruu metodeina käytin: teemahaastattelua, havainnointia, valokuvia, videoita ja matkapäiväkirjaa. Haastattelutilanteiden lisäksi vietin paljon aikaa haastateltujen turistien kanssa. Haastatteluiden ulkopuolella tekemäni havainnot auttoivat saamaan kattavammat käsitykset henkilöistä ja heidän kokemuksistaan, sillä joskus se, mitä ihmiset haastattelussa sanovat, voi poiketa todellisuudesta. Tätä tutkimusta varten haastattelin yhteensä 13 kansainvälistä turistia yhdeksästä eri maasta. Demografisten ja psykografisten segmentointikriteerien pohjalta ehdotan 4 erilaista typologiaa, joihin nämä turistit voi karkeasti jaotella: Nuoret ja nälkäiset, Opportunistit, Maailmanmatkaajat ja Varttuneet matkaajat. Mikä veti näitä erilaisia turisteja Siperiaan, oli sitä ympäröivä mysteeri. Joillekin matkan tekeminen oli ollut unelma jo pitkään. Koska matkustajilla ei ollut paljoakaan tietoa tai odotuksia TSR: stä, he olivat yleensä positiivisesti yllättyneitä matkastaan. Se, mikä näytti tuovan kokemuksellista arvoa turisteille, olivat ainutlaatuiset interaktiot muiden matkailijoiden sekä erityisesti paikallisten kanssa ja saavutuksen tunne maailman pisimmän rautatien ylittämisestä. Matkailun suosion kasvaessa ihmiset etsivät uusia kohteita, jotka voivat tarjota heille jännitystä ja ainutlaatuisia kokemuksia. Tästä syystä uskon, että Venäjä, ja etenkin sen vähemmän ”länsimaalaistuneet” osat, kuten Siperia, tulevat houkuttelemaan turisteja tulevaisuudessa. Venäjän tulisi ymmärtää TSR:n turismimarkkinapotentiaali ja rohkaista matkailulaitoksia, matkatoimistoja ja RZD:tä (Venäjän kansallinen rautatieyhtiö) kehittämään palvelujaan matkan houkuttelevuuden parantamiseksi.
Keywords: Trans-Siberian Railway, travel motivation, tourist experience, ethnography, Russia